Community-associated Methicillin-resistant Staphylococcus aureus pericarditis in an immunocompetent patient. (2022) - Jevtic, Dorde; Dumic, Igor; Adam, Adam; Barsoum, Michel K.; Hanna, Richard D.; Sprecher, Lawrence J.; Antic, Marina; Radovanovic, Milan
Abstract: Background: Pericarditis caused by Methicillin-resistant Staphylococcus aureus (MRSA) is a rare infection, often seen in patients with chronic kidney disease, immunosuppression, or previous pericardial disease. The presentation can be dramatic with acute illness leading to septic and/or obstructive shock due to pericardial tamponade. Occasionally disease can have a more protracted, indolent, subacute clinical course. Case report: We report a case of a 57-year-old male patient with a previous history of smoking and moderate alcohol use who presented with progressive dyspnea and cough. He was found to have a disseminated MRSA infection with pericarditis complicated by pericardial tamponade. Urgent pericardiocentesis yielded 1.1 liters of purulent fluid that grew MRSA. MRSA was also isolated from the blood and pleural fluid. The patient underwent left thoracotomy, decortication, and pericardial window and completed 3 weeks of intravenous vancomycin therapy, concluding in an excellent outcome. Conclusion: Bacterial pericarditis is an exceptionally rare form of pericarditis which been traditionally associated with chronic medical conditions requiring a prolonged healthcare stay. However, it has lately been observed in healthy individuals with social habits such as smoking and alcohol consumption. Bacterial pericarditis must be recognized in a timely fashion and managed aggressively to prevent a devastating outcome. A multidisciplinary approach is advised, which includes a combination of pericardial drainage and aggressive antibiotic therapy. Such treatment often yields a positive outcome and good long-term prognosis.